The birth of Korean cool how one nation is conquering the world through pop culture - Hong, Y. Euny (New York Picador, 2014)
"A FRESH, FUNNY, UP-CLOSE LOOK AT HOW SOUTH KOREA REMADE ITSELF AS THE WORLD'S POP CULTURE POWERHOUSE OF THE TWENTY-FIRST CENTURY By now, everyone in the world knows the song "Gangnam Style" and Psy, an instantly recognizable star. But the song's international popularity is no passing fad. "Gangnam Style" is only one tool in South Korea's extraordinarily elaborate and effective strategy to become a major world superpower by first becoming the world's number one pop culture exporter. As a child, Euny Hong moved from America to the Gangnam neighborhood in Seoul. She was a witness to the most accelerated part of South Korea's economic development, during which it leapfrogged from third-world military dictatorship to first-world liberal democracy on the cutting edge of global technology. The Birth of Korean Cool recounts how South Korea vaulted itself into the twenty-first century, becoming a global leader in business, technology, education, and pop culture.Featuring lively, in-depth reporting and numerous interviews with Koreans working in all areas of government and society, Euny Hong reveals how a really uncool country became cool, and how a nation that once banned miniskirts, long hair on men, and rock 'n' roll could come to mass produce boy bands, soap operas, and the world's most popular smartphone"--
"Euny Hong grew up in Gangnam, the posh Seoul neighborhood Psy is mocking in his viral sensation, "Gangnam Style." She knows the song's popularity is not just a fluke but rather the result of Hallyu--the Korean wave--just another sign of South Korea's increasing popularity around the world. The Birth of Korean Cool will show how South Korea vaulted itself into the twenty-first century, becoming a global leader in business, technology, education, and pop culture. Along the way we meet teachers, cultural critics, Michelin-starred chefs, pop music superstars, and government ministers in charge of creating boy bands with highly synchronized dance moves. The strict rigors of the Korean education system now lead to a society that works and plays hard--with a Ministry of Culture that churns out movies, television dramas, pop bands, and video games exported throughout the world. Euny Hong reveals how a really uncool country became cool, and how a nation that once banned miniskirts, long hair on men, and rock and roll could come to be known for its pop music and the smart phone in everyone's pocket. Welcome to South Korea: The Brand. - Fascinating first-hand reporting from a wide cross-section of Korean society from a young, hip voice - For readers of The Fortune Cookie Chronicles, Fresh Off the Boat, and JapanAmerica"--
Keywords: Hong, Y. Euny; Cultura popular -- Korea (South); Korea (South) -- Vida social y costumbres; Hallyu